Mathematical Learning Disabilities a Neurological View and the role of Digital Technologies - Galitskaya, Viktoriya N (Eximia, 2023)
The present article is a literature review of recent researches that have to do with children with mathematical learning disabilities especially dyscalculia and ageometria. Our focus is on researches regarding neurosciences, mainly on the brain structure and the areas where various mathematical processes are performed. In addition, we present researches that show the role of hippocampus during arithmetic problem solving